2016
DOI: 10.4038/gmj.v20i2.7933
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions on hospital food service at Teaching Hospital, Karapitiya

Abstract: Background: Hospital diet is an integral part of the management of inward patients. The quality of hospital food plays a major role in determining the overall satisfaction of patients with regards to their hospital stay. Objective: To investigate the level of patient satisfaction with regards to the diet supplied at Teaching Hospital (TH), Karapitiya. Methods: A descriptive, cross sectional study was conducted among 316 patients who received inward treatment at TH Karapitiya and consumed hospital diet. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Patients consider hospital meals to be undesirable due to issues related to quality of food such as menu items, portion size, taste, temperature, texture and variety of food as well as poor service standards such as tray presentation, sanitation, availability of nutritional information and responsiveness to food problems (12)(13)(14)(15)(16)(17)(18)(19)(20). Attitudes of staff serving food and absence of disturbance are also related to satisfaction with food service (21) Research has proven that patient satisfaction on hospital food service can be improved by interventions that improve meal delivery (1,2) and quality of food (21).…”
Section: Patient Satisfaction With Hospital Mealsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients consider hospital meals to be undesirable due to issues related to quality of food such as menu items, portion size, taste, temperature, texture and variety of food as well as poor service standards such as tray presentation, sanitation, availability of nutritional information and responsiveness to food problems (12)(13)(14)(15)(16)(17)(18)(19)(20). Attitudes of staff serving food and absence of disturbance are also related to satisfaction with food service (21) Research has proven that patient satisfaction on hospital food service can be improved by interventions that improve meal delivery (1,2) and quality of food (21).…”
Section: Patient Satisfaction With Hospital Mealsmentioning
confidence: 99%
“…A situational analysis involving four major hospitals in Galle and Rathnapura districts revealed that only 30% or less of the inward patients consume hospital meals (unpublished data). A study conducted at Teaching Hospital Karapitiya found that only 27% of inward patient consumed hospital diet (20). The major reasons for poor consumption were the tastelessness, unpleasant aroma of food and shyness to eat hospital food.…”
Section: Improving Food Service Standards In Sri Lankan Health Care Smentioning
confidence: 99%
“…Previous studies reported that the food service quality was evaluated by in-patients based on several factors such as nutritional value, taste, texture, variety, sanitation, portion size, temperature, meal time and servers' characteristics (Fallon et al, 2008;Theurer, 2011;Wright et al, 2006). It was suggested that the patients' attitudes and their level of satisfaction with hospital food service depend mainly on these factors (Fernando & Wijesinghe, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There have been mixed results to date with respect to predictors of patient perceptions of hospital food. Some have suggested patient traits have no effect, [33][34][35][36] whereas others note that gender 23,28,29,37 and age 23,28,29,38,39 are important. Mealtime accessibility challenges, 40 diet type 23,29 and length of stay 23,29,34 also influence perceptions of hospital food.…”
mentioning
confidence: 99%
“…Mealtime accessibility challenges, 40 diet type 23,29 and length of stay 23,29,34 also influence perceptions of hospital food. Because most of these studies were conducted at a single site, 23,28,29,[33][34][35][36]38,39 generalisability is limited. Furthermore, some used unvalidated methods of assessing patients' food quality perceptions.…”
mentioning
confidence: 99%